2019
DOI: 10.1177/0890334419845338
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Influence of Chondroitin Sulfate, a Component of Human Milk, on Intestinal Bacterial Invasion and Translocation

Abstract: Background: Human milk is known to be protective against necrotizing enterocolitis, a devastating intestinal inflammatory disease affecting the preterm population. Although the pathogenesis of necrotizing enterocolitis is yet to be solidified, intestinal integrity dysfunction, bacterial invasion and/or translocation, and inflammation may play important roles. Glycosaminoglycans, compounds naturally prevalent in both human milk and the intestine, are thought to be anti-inflammatory and capable of altering bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 91 publications
1
14
0
Order By: Relevance
“…Newburg and colleagues showed CS can inhibit the binding of HIV’s glycoprotein, gp120 to the host cell CD4 receptor [ 115 ]. This study is consistent with another which showed that CS in isolation can be protective to an intestinal in vitro system [ 136 ].…”
Section: Chondroitin Sulphatesupporting
confidence: 93%
“…Newburg and colleagues showed CS can inhibit the binding of HIV’s glycoprotein, gp120 to the host cell CD4 receptor [ 115 ]. This study is consistent with another which showed that CS in isolation can be protective to an intestinal in vitro system [ 136 ].…”
Section: Chondroitin Sulphatesupporting
confidence: 93%
“…The key results of previous studies in this field need to be discussed. Some studies found that colostrum was effective in reducing the rate of NEC, revealing its effect in building up immunity [11,[39][40][41][42]. Term babies could suck their mothers' nipples to obtain breast milk and their immunity would be triggered through the first bite with colostrum being served as stimulator [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…A dose-dependent reduction in bacterial invasion occurred with CS (M ± SEM), with 750 µg/mL showing significantly lower bacterial invasion compared to control (** p = 0.0071; eta-squared = 0.0944); (b) CS at 750 µg/mL was significantly protective by the third hour of inoculation (M ± SEM, ** p = 0.0018). (Reprinted with permission of authors and SAGE Publishing [194]).…”
Section: Discussionmentioning
confidence: 99%
“…Our group has also directly interrogated the ability of CS, the most common GAG in HM [146], to limit both bacterial invasion ( Figure 3a) and translocation ( Figure 3b) in T84 colonocyte monolayers, an in vitro model of the intestinal epithelium [194]. CS, at a concentration of 750 µg/mL given prophylactically for 48 h prior to bacterial challenge, reduces invasion and translocation of SCB34 Escherichia coli, an invasive, multi-drug resistant bacterial strain isolated from a neonatal early-onset sepsis case [195], by 75% compared to control.…”
Section: Glycosaminoglycan Protection Against Necmentioning
confidence: 99%